Stabilization of Pluronic P-105 Micelles with an Interpenetrating Network of N,N-Diethylacrylamide - Pruitt, John D. (2000)
N,N-Diethylacrylamide (NNDEA) was polymerized in the presence of Pluronic P-105 micelles. The polymerizations resulted in an interpenetrating network of poly(NNDEA) and P-105 that stabilized the micelles at concentrations below the critical micellar concentration of free P-105. The NNDEA was cross-linked with N,N′-bis(acryoyl)cystamine (BAC), and the degree of micellar stability was determined using dynamic light scattering and the fluorescent probe diphenylhexatriene (DPH).The increased micellar stability was not permanent and disappeared over a time period of days to weeks.